The Health Services White Paper : The Labour Party's policy
1944-09 1944 1940s 22 pages - 20 - 4. The State, through University Grants, already pays half the purely educational costs of medical training. It should in future pay the whole cost. And there should be available maintenance grants for every student who needs them. 5. Since the number of students working at each hospital must be strictly limited if they are to get full practical training, it follows that there must be a considerable increase in the number of teaching hospitals and medical schools. Some of the larger municipal hospitals should be utilised for this purpose, and admission to all new schools should be on equal terms for both sexes. 9. Research. It is on the results achieved by medical research that the practice of medicine depends. The. annual expenditure of the Medical Research Council is in the region of £250,000 - less than a five-hundredth of the proposed expenditure on the new national health service. The Labour Party considers that research must be given a more prominent place in the scale of values then it occupies at present. Expenditure should be allocated in millions rather than hundreds of thousands. In particular research workers should be no less well paid than doctors in active practice; team research should be developed to the full; and a Social Research Council, analagous [analogous] to the Medical Research Council should be set up. The nucleus for the research work of such a council already exists in the Wartime Social Survey. 10. The Promotion of Health. The White Paper is concerned with a plan for a complete treatment service. The promotion of health depends less on the medical services as such than on good food, good housing, sound town-planning, full employment, end satisfactory conditions of work and the right use of leisure. Each of these will affect the community as a whole. But the reorganisation of medical services offers the possibility of developing among doctors new approaches to their work:- 1. With more time at their disposal doctors will be able to play a bigger part in the prevention of disease among their individual patients. 2. For the first time it will be possible for doctors to think about the promotion of the health of their individual patients. At present, we know little about this. But a body of knowledge must be built up as quickly as possible. Thorough periodical health overhauls may point the way; but before they can become general, we shall need many more doctors. 3. Health education is only just beginning. Doctors are not taught how to teach their patients. Yet this individual teaching is perhaps the most valuable way of making the public look on health and disease as things which are to be dealt with by science, reason, and common sense, rather than by magic and patent medicines. The Labour Party looks to the new health service to create within the medical profession a new attitude to health, and education for health. This will require an extension of research in the field of individual health. The Ministry of Health's activities in the field of health education should be considerably extended. 292/847/3/166